Bupivacaine Field Block With Clonidine for Postoperative Pain Control in Posterior Spine Approaches: A Randomized Double‐Blind Trial. Issue 6 (June 2018) - Abdel Hay, Joe; Kobaiter‐Maarrawi, Sandra; Tabet, Patrick; Moussa, Ronald; Rizk, Tony; Nohra, Georges; Okais, Nabil; Samaha, Elie; Maarrawi, Jospeh
Abstract: BACKGROUND : The synergistic effect of clonidine with bupivacaine, well established in peripheral nerve blocks, remains controversial in local field block for postoperative analgesia. OBJECTIVE : To investigate the potential analgesic benefit of adding clonidine to bupivacaine during preincisional field block in posterior approaches for spine surgeries. METHODS : Two hundred twenty‐five patients were enrolled in this study and underwent lumbar spinal fusion (n = 80) lumbar laminectomy (n = 25) lumbar microdiscectomy (n = 94) or cervical laminectomy (n = 26). In each surgical subgroup, patients were randomly assigned in a double‐blinded fashion to receive either 20 mL of 0.25% bupivacaine alone (control group, n = 109) or with 150 μg clonidine (clonidine group, n = 116) in the form of a preincisional field block. Outcome parameters included area under the curve of pain from postoperative day D0 to D8 and rescue morphine consumption from D0 to D3. RESULTS : The area under the curve was reduced in the clonidine group, particularly in the microdiscectomy subgroup, and without reaching statistical significance in the cervical laminectomy subgroup. Total rescue morphine consumption was reduced in the clonidine group, particularly at D1‐D2, a benefit that was exclusive to the lumbar stenosis and lumbar fusion subgroups. Field block with clonidine, surgical subgroup, and the presence of preoperative spinal pain were factors independently influencing postoperative wound pain in multivariate analysis. CONCLUSION : The addition of clonidine to local preincisional field block with bupivacaine resulted in better and prolonged postoperative analgesia in posterior lumbar spine surgeries, an effect that was more pronounced in patients with no preoperative spinal pain.